2011
DOI: 10.3138/jvme.38.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Online Professional Network for Veterinary Education: The NOVICE Project

Abstract: An online professional network for veterinarians, veterinary students, veterinary educationalists, and ICT (Information and Communication Technology) educationalists is being developed under the EU (European Union) Lifelong Learning Programme. The network uses Web 2.0, a term used to describe the new, more interactive version of the Internet, and includes tools such as wikis, blogs, and discussion boards. Focus groups conducted with qualified and student veterinarians within the project's five founding countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…7,38,41 Reports in the literature show that low and medium fidelity models can be just as effective as high fidelity so there is some educational merit in this cost savings. 74 Additionally, there is a growing preparedness to share ideas and the 'recipes' for making models and sourcing materials via forums 40 and skills videos via YouTube. 53 Assessing student performance is also an added cost that was not clearly separated out and identified in our survey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,38,41 Reports in the literature show that low and medium fidelity models can be just as effective as high fidelity so there is some educational merit in this cost savings. 74 Additionally, there is a growing preparedness to share ideas and the 'recipes' for making models and sourcing materials via forums 40 and skills videos via YouTube. 53 Assessing student performance is also an added cost that was not clearly separated out and identified in our survey.…”
Section: Discussionmentioning
confidence: 99%
“…at International Veterinary Simulation in Teaching (InVeST), Veterinary Education Symposium (VetEd), Veterinary Educator Collaborative (VEC) and Association for Medical Education in Europe (AMEE), and from lists in the 'Veterinary Clinical Skills & Simulation' group in the online forum 'NOVICE' . 40 The survey was distributed via email to a known contact at each veterinary college on the list with a covering letter and an embedded link requesting that the addressee complete the survey or forward it to someone more appropriate. Respondents could remain anonymous but were asked to supply details if they were prepared to be contacted by the project team for follow-up question or should clarification be required.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another snapshot of social networks in higher education shows that they have not yet been used for teaching purposes but further studies are necessary to determine suitability for professional exchange and teaching [73]. Initial studies in this field have been initiated in veterinary medicine [3]. But this makes training for students and teachers in Web 2.0 indispensable [77], as these studies have shown (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Επιπρόσθετα, οι χρήστες μπορούν εύκολα να δημιουργήσουν το δικό τους προφίλ, παρουσιάζοντας πληροφορίες (επιστημονικά ενδιαφέροντα, στοιχεία επικοινωνίας, κ.ά. ), να συνδεθούν με τους φίλους τους και να διαμοιράσουν υλικό, θέτοντας οι ίδιοι το επίπεδο πρόσβασης σε πρόσωπα ή ομάδες (Baillie et al, 2011). Ακόμη, μέσω του Elgg παρέχονται όλες οι σύγχρονες εφαρμογές κοινωνικής δικτύωσης (ιστολόγια, wikis κ.ά.…”
unclassified